Impact of Hamstring Graft on Hamstring Peak Torque and Maximum Effective Angle After Anterior Cruciate Ligament Reconstruction: An Exploratory and Preliminary Study - Ismail Bouzekraoui Alaoui; Ayrton Moiroux-Sahraoui; Jean Mazeas; Georgios Kakavas; Maciej Biały; Maurice Douryang; Florian Forelli (Bioengineering)
Purpose: Anterior cruciate ligament reconstruction (ACLR) using the hamstring graft is commonly performed to restore knee stability; however, it induces significant neuromuscular and biomechanical changes, particularly in the hamstring. This study aimed to evaluate the changes in maximum effective angle, hamstring strength, and hamstring-to-quadriceps (H/Q) strength ratio at 3 and 6 months post-ACLR and compare these outcomes to a control group. Methods: This prospective controlled study included 20 ACLR patients and 20 age- and gender-matched controls. Hamstring peak torque, maximum effective angle (MEA), and the H/Q ratio were assessed using isokinetic dynamometry at 60°/s. The ACLR group was evaluated postoperatively at 3 and 6 months, while the control group underwent a single evaluation. Results: At 3 and 6 months, the ACLR group exhibited significantly lower MEA (26.3° ± 8.2 and 28.2° ± 9.4) compared to the control group (36.4° ± 12.0; p < 0.01). Hamstring peak torque and H/Q ratios were also lower in the ACLR group but showed slight improvements over time. The H/Q ratio increased significantly between 3 and 6 months (51% to 56%; p = 0.041). Conclusion: The use of hamstring graft in ACLR leads to persistent MEA and strength deficits despite rehabilitation. Advanced, targeted rehabilitation protocols are essential to address these deficits, optimize recovery, and reduce the risk of reinjury.